TMIC-10. AUTOPSY STUDY ON THE EFFECTS OF TUMOR TREATMENT FIELDS IN RECURRENT GLIOBLASTOMA: PRELIMINARY RESULTS. (5th November 2018) - Barrington, Alexander; Hurrell, Sarah; Laviolette, Peter
Abstract: BACKGROUND: Treatment of recurrent glioblastoma using tumor treatment fields (TTFields) has recently been approved. This resulted from a recent clinical trial that showed better quality of life and comparable overall survival. Low-intensity, alternating frequency electric fields, known as TTFields, have been shown to disrupt cell division and subsequently tumor growth. Apoptosis and cell cycle arrest have been seen in vitro, and shown in mice and rabbit tumor models. Glioblastoma patients who have undergone TTField therapy have not yet been assessed at autopsy to determine both the pathological signature of TTField therapy, and the pattern of failure. METHODS: Whole brain samples were acquired and analyzed pathologically from six recurrent GBM patients at autopsy. Three patients served as controls and three were considered test patients who had undergone TTField therapy. Tissue samples were acquired from regions suspicious of tumor and treatment effects. Samples were paraffin embedded and hematoxylin and eosin (H&E) stained, and pathologically reviewed by a board certified pathologist. Pathomic features of interest were extracted from each sample, including texture features and cellular morphometrics. Samples were then compared statistically. RESULTS: Regions of necrosis and cellular debris were more prevalent in the patients who underwent TTField therapy. Some pathomic features of interest differed significantly between the two groups. CONCLUSION: These findings suggest there is increased apoptosis in patients treated with TTFields compared to those on chemoradiation alone. Recruitment is ongoing for expansion of this study.